Vegetative growth of Conilon coffee plants under two water conditions in the Atlantic region of Bahia State, Brazil - André Monzoli Covre; Fábio Luiz Partelli; Robson Bonomo; Heder Braun; Cláudio Pagotto Ronchi (Acta Scientiarum. Agronomy, 2016)
Extreme temperatures and persistent water stress stand out among the main factors that restrict the vegetative growth and productivity of Coffea canephora. The objective of this study was to evaluate the vegetative growth of orthotropic and plagiotropic branches of C. canephora under non-irrigated and irrigated conditions, and their correlation with climatic factors in the Atlantic region of Bahia State, Brazil. The experiment was established with two treatments (non-irrigated and irrigated) in a completely random design with 14 replicates. One orthotropic and four plagiotropic branches were labelled on each plant. During the two-year experimental period, the growth of these branches was evaluated at 14-day intervals. Two harvests were performed to obtain productivity data. In summary, it was confirmed that irrigation resulted in an increased productivity of Conilon coffee in the Atlantic region of Bahia, Brazil. The growth rate of the orthotropic and plagiotropic branches was higher in irrigated plants. The growth rate of the plagiotropic branches was limited by the fruit load capacity. The growth rate of C. canephora branches was not limited by the minimum average air temperature in the Atlantic region of Bahia, Brazil.